(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2003)
Forensic medicine personnel who come in direct contact with the body fluids, soft tissues of the dead and skeletal material in various stages of decomposition ,are at continuous risk of acquiring various kinds of infections including blood-borne viral and other bacterial infections. However, limited data are available regarding these risks to persons who are usually exposed to large number of traumatized bodies in India, a country that has an existing and growing HIV epidemic and high hepatitis virus seroprevalence. In the pre-antibiotic and pre-vaccine eras, an occupational infection was a serious threat for a forensic medicine and general health care person, but many such fears were allayed with the advent of antibiotics, vaccines and infectious disease eradication and elimination programmes. Safety is an issue not only relevant to the team performing the autopsy, but also has direct implications regarding the protection of the environment. Prevention strategies include immunization, exposure avoidance by the use of Members universal precautions.